Knowledge and Perceptions of Adolescent Girls on HIV/AIDs and Family Planning (Siddhajyoti Interdisciplinary Journal, 2024)
Nepali adolescent girls face distinct challenges in HIV/AIDS and family planning, necessitating a nuanced understanding. Global concerns for adolescent reproductive health and rights, emphasized in international conferences, apply to Nepal’s struggle with HIV/ AIDS, particularly among young people. In this context, this studyaims to investigate knowledge and perceptions of adolescent girls on HIV/AIDS in Nepali context. Moreover, this study concerns on exploring cultural norms and social determinants that affect family planning among adolescents in Nepal. The researcher has employed survey research design of quantitative research by taking data from 111 late adolescent girls (15-19 years) through questionnaires in Sindhuli. Findings reveal age-related influences on reproductive health knowledge and perceptions. While family planning awareness is widespread, specific method knowledge disparities exist. Despite challenges, most exhibit positive perceptions and behaviours towards people living with HIV/AIDS. This research contributes evidence-based interventions, emphasizing the need for context-specific strategies to address the reproductive health needs of adolescent girls in Nepal.